The global carbon cycle and climate change : scaling ecological energetics from organism to the biosphere - Reichle, David E. (Elsevier, 2020)
The Global Carbon Cycle and Climate Change examines the global carbon cycle and the energy balance of the biosphere, following carbon and energy through increasingly complex levels of metabolism from cells to ecosystems. Utilizing scientific explanations, analyses of ecosystem functions, extensive references, and cutting-edge examples of energy flow in ecosystems, it is an essential resource to aid in understanding the scientific basis of the role played by ecological systems in climate change. This book addresses the need to understand the global carbon cycle and the interrelationships among the disciplines of biology, chemistry, and physics in a holistic perspective. The Global Carbon Cycle and Climate Change is a compendium of easily accessible, technical information that provides a clear understanding of energy flow, ecosystem dynamics, the biosphere, and climate change. --